1998
DOI: 10.1891/0886-6708.13.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Partner Violence and Sexual HIV-Risk Behaviors Among Women in an Inner-City Emergency Department

Abstract: This study examines the relationship between partner violence and sexual risk behaviors in a sample of predominantly Latina and African American women who sought medical care from a New York City hospital emergency department. Eligibility criteria selected women between the ages of 18 and 55, who were sexually active in the past 90 days, and were triaged to nonemergency care. The interview addressed demographics, partner violence, childhood abuse, sexual behavior, and drug and alcohol use. Multiple logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 0 publications
5
76
0
Order By: Relevance
“…[45][46][47] In addition, one study of sexually active women surveyed in an emergency department setting revealed that after adjusting for childhood abuse and age, women who have been abused in the past in comparison to non abused women were almost 5 times more likely to have contracted an sexually transmitted disease and 4.2 times more likely to have sex with a high-risk partner in the month prior to the interview. 48 Sexually abused men were significantly more likely than homosexual and bisexual men with no history of sex abuse to engage in HIV risk behaviors and to be HIV positive. 49 Further, one study noted that a history of multiple abuse during adolescence and young adulthood had a greater association with HIV infection than just one sexual abuse event in adolescence.…”
Section: Discussionmentioning
confidence: 98%
“…[45][46][47] In addition, one study of sexually active women surveyed in an emergency department setting revealed that after adjusting for childhood abuse and age, women who have been abused in the past in comparison to non abused women were almost 5 times more likely to have contracted an sexually transmitted disease and 4.2 times more likely to have sex with a high-risk partner in the month prior to the interview. 48 Sexually abused men were significantly more likely than homosexual and bisexual men with no history of sex abuse to engage in HIV risk behaviors and to be HIV positive. 49 Further, one study noted that a history of multiple abuse during adolescence and young adulthood had a greater association with HIV infection than just one sexual abuse event in adolescence.…”
Section: Discussionmentioning
confidence: 98%
“…Estimates of recent partner abuse among ED patients range from 12 to 19% and of lifetime partner abuse from 44 to 54% (1)(2)(3)(4)(5). Substance use is a common comorbid condition with partner abuse; studies in a wide variety of ED settings have reported high rates of substance use among partner abuse survivors, ranging from 29-63% for drug use (5-8) and 19-64% for alcohol use (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the relationship between experiencing IPV and HIV/STI transmission risks among heterosexual women has elucidated several pathways linking IPV and HIV/STI transmission risks that may also exist among male perpetrators, including (1) engaging in unprotected sex, 14,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] (2) higher rates of STIs, 29,[35][36][37][38][39] (3) sex with multiple sexual partners, 28,29,40 (4) disclosure of an STI or positive HIV status, 41,42 (5) trading sex for drugs or money, 36,43 (6) having a risky sexual partner (e.g., one who injects drugs is HIV-positive and/or has had sex with multiple partners), 28,29,33,36,38,[43][44][45] (7) forced sex, 43,46,47 and (8) injecting drug use. 20 This study builds on previous research linking perpetration of IPV and HIV/STI transmission risks by examining the...…”
Section: Introductionmentioning
confidence: 99%